2008
DOI: 10.1111/j.1365-2710.2008.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of patients receiving a pharmaceutical care service in Sweden

Abstract: This study demonstrates that the total number of patients enrolled in a PC service predicts whether follow-up evaluations will take place or not more than do patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
11
1
1
Order By: Relevance
“…Practitioners did not routinely introduce themselves by name, which is more professional and respectful to the patients. Emphasising the possibility of receiving followup evaluations at the initial consultation of the PC service could potentially increase the moderate follow up rate [30] in this service.…”
Section: Discussionmentioning
confidence: 96%
“…Practitioners did not routinely introduce themselves by name, which is more professional and respectful to the patients. Emphasising the possibility of receiving followup evaluations at the initial consultation of the PC service could potentially increase the moderate follow up rate [30] in this service.…”
Section: Discussionmentioning
confidence: 96%
“…The pharmacy business itself might encourage pharmacists to provide pharmaceutical care service for the purpose of publicity and marketing of their business. The age of the responsible pharmacist also plays a crucial role in providing pharmaceutical care services 6,7. To implement pharmaceutical care under such circumstances and its effects is considered a challenge to pharmacy associations, managers, and individual pharmacists who are in a position to improve this element of patient care 8.…”
Section: Introductionmentioning
confidence: 99%
“…Educational intervention is part of pharmacotherapy follow‐up and contributes to better clinical outcomes as pharmaceutical interventions can enhance adherence to treatment . A retrospective study in Sweden showed that follow‐up interventions led to a better‐perceived outcome in 46.3% of cases …”
Section: Discussionmentioning
confidence: 99%